Análise fito-citogenotóxica de concentrações ambientalmente relevantes de pesticidas - Miranda, Luanna Alves (2022)
Brazil is one of the largest importers and consumers of pesticides in the world. Therefore, the intensive and indiscriminate use of these compounds is worrisome due to contamination of the aquatic environment. One of the associated problems is the exposure of non-target organisms to pesticides, causing clastogenic and also aneugenic damage, with alterations in the cell cycle, mutations and cell death. Thus, this study aimed to investigate whether environmentally relevant concentrations of the pesticides glyphosate, 2,4-D, imidacloprid and iprodione, reported by CONAMA Resolution nº 375 (2005) and/or found in surface and supply waters cause phyto-toxic effects. cytogenotoxic agents in Allium cepa. Pesticides were tested singly and in combination. The analyzes performed were: germination index, germination speed, root growth, mitotic index, frequency of aberrant cells and cell cycle analysis by flow cytometry. It was found that pesticides and mixtures inhibited the cell division cycle (inhibition of the mitotic index, increased particle frequency in sub-G1, increased cells in G0/G1 and reduced nuclei in S and G2/M phases) induced the formation of aberrant cells and increased the coefficient of variation of G1, culminating in the reduction of germination index, germination speed and root length. The results of this study indicated that the tested pesticides and mixtures pose a risk to non-target organisms.